THE THEORY OF INSTRUCTIONAL OBJECTIVES AND ITS PLACE IN A SCHOOL’S EVALUATION PROCEDURES - Yakasai, M. I. (Sokoto Educational Review, 2020)
A Teacher’s role is not limited only to setting goals and assigning tasks and monitoring learners to realize the Instructional objectives. He is expected to account for the achievement by the learners, of the stated behavioural objectives. To realize this, a teacher embarks on evaluation procedures to determine the extent to which learners can be said to attain such behavioural objectives. Hence, a teacher need a ‘blue print to effectively carryout this function. This paper, therefore, examines the Bloom’s taxonomy of cognitive, psychomotor and affective domains so as to help teachers to clearly outline the experiences they are to measure as far as classroom evaluation is concerned.